Association between sinusitis and relapse and changes in the myeloperoxidase-antineutrophil cytoplasmic antibody in microscopic polyangiitis. - Hiroya Tanaka; Makoto Yamaguchi; Takayuki Katsuno; Hirokazu Sugiyama; Shiho Iwagaitsu; Hironobu Nobata; Hiroshi Kinashi; Shogo Banno; Takuji Ishimoto; Yasuhiko Ito (PLoS ONE, 2020)
Previous studies have evaluated the risk factors for relapse of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and the biomarkers of AAV for predicting relapse. However, little is known about the association between the presence of sinusitis and relapse and changes in the ANCA levels in AAV. This single-center, retrospective cohort study included 104 consecutive patients who were newly diagnosed with myeloperoxidase (MPO)-ANCA-positive microscopic polyangiitis (MPA) between 2006 and 2018 and were treated at the Aichi Medical University Hospital in Japan. The relationships between sinusitis and relapse of vasculitis and elevated MPO-ANCA levels were assessed using multivariate Cox proportional hazards models that were adjusted for clinically relevant factors. During the entire follow-up period (median, 24 months; interquartile range, 7-54 months), 93 (89.4%) patients achieved remission. After achieving remission, 38 (40.9%) patients experienced at least one relapse (13 [65.0%] in the sinusitis group; 25 [34.3%] in the non-sinusitis group). Sinusitis was identified as a significant predictor of relapse (adjusted hazard ratio: 2.41, 95% confidence interval [CI]: 1.19-4.88; P = 0.015). Furthermore, sinusitis was more likely to be associated with elevated MPO-ANCA levels (adjusted hazard ratio: 2.59, 95% CI: 1.14-5.92; P = 0.024). In conclusion, sinusitis was associated with a higher risk of relapse and elevated MPO-ANCA levels in MPA patients, suggesting that careful management may be required to reduce the risk of relapse in patients with sinusitis. Further studies are needed to elucidate the optimal treatment strategy for these patients.